A facile route to prepare cellulose-based films. (20th September 2016) - Xu, Qin; Chen, Chen; Rosswurm, Katelyn; Yao, Tianming; Janaswamy, Srinivas
Graphical abstract: Zn 2+ ions are effective in solubilizing cellulose and crosslink through Ca 2+ ions leading to stronger cellulose films. Highlights: Cellulose is solubilized in the presence of Zn 2+ ions. Zn 2+ ions hydrogen bond to the atom O3H leading to flexibility in the cellulose chains. Presence of Ca 2+ ions promotes nano fibrils and induces gelation in the Zn-cellulose solution. Tensile strength of the Zn-cellulose films is enhanced in the presence of Ca 2+ ions. These cellulose-based novel biodegradable films are potential for food, pharmaceutical and medicinal applications. Abstract: Cellulose is the most abundant renewable and biodegradable material available in nature. Its insoluble character in water as well as common organic and inorganic liquids, however, curtails the wholesome utility. The continuous rise for biodegradable products based on cellulose coupled with its intrinsic ability to form a viable substitute for the petroleum-based materials necessitates the critical need for solubilizing the cellulose. Herein, we demonstrate the feasibility of ZnCl2 solutions, especially the 64–72% concentrations, to dissolve cellulose. FTIR results suggest that Zn 2+ ions promote Zn⋯O3H interactions, which in-turn weaken the intrinsic O3H⋯O5 hydrogen bonds that are responsible for strengthening the cellulose chains. Interestingly, Ca 2+ ions promote interactions among the Zn-cellulose chains leading to the formation of nano fibrils and yield gelling solutions. The tensile strength of the Ca 2+ added Zn-cellulose films increases by around 250% compared to the Zn-cellulose films. Overall, utilization of inorganic salt solutions to solubilize and crosslink cellulose is cost-effective, recyclable and certainly stands out tall among the other available systems. More importantly, the proposed protocol is simple and is a "green" process, and thus its large-scale adaptability is quite feasible. We strongly believe that the outcome opens up a new window of opportunities for cellulose in the biomedical, pharmaceutical, food and non-food applications.